Dimensionamento de um sistema fotovoltaico fixo conectado à rede: estudo de caso do Campus Universitário de Abaetetuba - OLIVEIRA, Érika Matos de (2018)
The applications of solar photovoltaic are quite diverse and can be used as a source in isolated or connected to the network. This study considers the design of a photovoltaic system connected to the network, installed in the block of the colleges, laboratories and in the parking lot of University Campus Abaetetuba Federal University of Pará. Firstly made a detailed analysis of the facilities of the blocks and payload type installed in each environment. From this, an estimate was made of the monthly consumption in order to obtain a load curve consumption. Data collection solarimetric this region is made from the use of software Radiasol2 developed by "Universidade Federal do Rio Grande do Sul." After the acquisition of all data, calculations are performed for the design of a system that can meet the demands of the blocks from the analysis of three crystalline silicon technologies (namely: monocrystalline, polycrystalline and amorphous). Also shown is the scaling with the same three technologies for parking Campus, in order to expand power generation. To conclude is presented an economic analysis of the implementation of photovoltaic system based on the estimated electricity production system, as well as the total cost of the installation, the calculation of energy savings and how long the investment made in the installation of the photovoltaic system will be paid.